Temperature-dependent vibrational spectroscopy to study order-disorder transitions in charge transfer complexes - Isaac, Rohan; Goetz, Katelyn; Roberts, Drew (AIP Advances, 2018)
Charge-transfer (CT) complexes are a promising class of materials for the semiconductor industry because of their versatile properties. This class of compounds shows a variety of phase transitions, which are of interest because of their potential impact on the electronic characteristics. Here temperature-dependent vibrational spectroscopy is used to study structural phase transitions in a set of organic CT complexes. Splitting and broadening of infrared-active phonons in the complex formed between pyrene and pyromellitic dianhydride (PMDA) confirm the structural transition is of the order-disorder type and complement previous x-ray diffraction (XRD) results. We show that this technique is a powerful tool to characterize transitions, and apply it to a range of binary CT complexes composed of polyaromatic hyrdocarbons (anthracene, perylene, phenanthrene, pyrene, and stilbene) and PMDA. We extend the understanding of transitions in perylene-PMDA and pyrene-PMDA, and show that there are no order-disorder transitions present in anthracene-PMDA, stilbene-PMDA and phenanthrene-PMDA in the temperature range investigated here.
Gesehen am 18.02.2020